Why that instrument? A bibliographic study of the reasons instruments are chosen by music therapy clients. Issue 5 (20th October 2017) - Gilboa, Avi; Almog, Yael
ABSTRACT: Music therapy clients' musical instrument choices and their underlying reasoning can be very useful in understanding the client's inner world. To shed light on this subject, we conducted a bibliographic study in which we surveyed four leading music therapy journals (British Journal of Music Therapy, Journal of Music Therapy, Music Therapy Perspectives, and Nordic Journal of Music Therapy) and leading music therapy books that contain case studies and clinical vignettes. Fifty-three examples were found where the client explicitly chose an instrument and the choice was explicitly interpreted by the client or the music therapist. An analysis of these examples revealed two dimensions by which instrumental choices are made: (1) The way the instrument is used (sensorially or symbolically); and (2) The attributes of the instrument (its sound, shape, or bodily action made when interacting with the instrument). The findings are discussed in light of existing music therapy theories. Recommendations for further studies are suggested.